ENVIRONMENT-BASED VILLAGE DEVELOPMENT IN BANJAR KEMUNING VILLAGE SEDATI DISTRICT SIDOARJO REGENCY - A. Fikri Amiruddin Ihsani; Hengki Hendra Pradana; Wiwik Suatin; Md. Mosaddek Billah (Jurnal Abdimas UNU Blitar, 2023)
In this service-based research, there are two focus studies, namely how the role of government and society in environmental-based development programs in Banjar Kemuning Village, Sedati District, Sidoarjo Regency and what are the driving and inhibiting factors for environmental-based development programs in Banjar Kemuning Village, Sedati District, Sidoarjo Regency. This study uses qualitative methods through the approach of observation, interviews, observations and documentation in data collection. The qualitative research method used aims to describe accurately the characteristics of individuals, circumstances, symptoms or certain groups in society. The theory used to analyze the phenomenon in this service-based research is Talcott Parson's Structural Functional theory with the AGIL concept. The results of this service-based research carried out in Banjar Kemuning Village, Sedati District, Sidoarjo Regency include: a) The role of the local government is as a stabilizer (stabilizing social, economic, and political), as an innovator or thinker in development, as a modernizer that is bringing to a modern direction. , and as a pioneer and implementer. b) The role of the community is as a participant in their participation in the development process. In this case, there are several factors that occur in the development process including: first, the inhibiting factors namely poverty, inequality, community income, failure of transformation and the decline of local institutions in rural communities. Second, the driving factor is the unity of the community to advance development with the aim of making the village more developed